2003
DOI: 10.1111/j.1651-2227.2003.tb02479.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized study of nasal continuous positive airway pressure in the preterm infant with respiratory distress syndrome

Abstract: Aim: To evaluate whether very preterm babies can be extubated successfully to nasal continuous positive airway pressure (nCPAP) within one hour of birth after receiving one dose of surfactant in the treatment of respiratory distress syndrome (RDS). Methods: Forty‐two infants of 25 to 28+6 wk of gestation were intubated at birth and given one dose of surfactant. They were then randomized within one hour of birth to either continue with conventional ventilation or to be extubated to nCPAP. Results: Eight out of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 22 publications
2
20
0
1
Order By: Relevance
“…The use of surfactant and NCPAP decreased the need for mechanical ventilation from 100% in the control group to 62% in the NCPAP group. 28 Similar results were published by Dani et al 29 showing a lesser need for mechanical ventilation in patients who after administration of surfactant were randomized to NCPAP vs mechanical ventilation.…”
Section: Cpap Prophylaxis Vs Treatmentsupporting
confidence: 79%
“…The use of surfactant and NCPAP decreased the need for mechanical ventilation from 100% in the control group to 62% in the NCPAP group. 28 Similar results were published by Dani et al 29 showing a lesser need for mechanical ventilation in patients who after administration of surfactant were randomized to NCPAP vs mechanical ventilation.…”
Section: Cpap Prophylaxis Vs Treatmentsupporting
confidence: 79%
“…The failure to make an impact on the incidence of BPD despite decreasing the amount of time spent on the ventilator has been shown in previous studies evaluating NCPAP. 13,19 Unexpectedly, we found improved growth of our infants in the HFNC group. Although we have maintained the same nutritionist, enteral feeding practices, and aggressive parenteral nutrition support in our unit over the entire period of the study, it is difficult to attribute this improvement solely to the HFNC without a prospective randomized study.…”
mentioning
confidence: 58%
“…In this small-scale study, surfactant treatment significantly reduced the need for subsequent mechanical ventilation (43% in surfactant-treated infants, as compared with 85% in controls, p = 0.003). Several additional trials using INSURE followed [31,36,37,38,39]. While some of these studies demonstrated a significantly decreased need for mechanical ventilation after INSURE [37,38], this apparent benefit did not translate into decreased rates of mortality or BPD [40].…”
Section: The 2000s: Old Roads Revisitedmentioning
confidence: 99%
“…Although experience with early CPAP to stabilize preterm infants and avoid invasive mechanical ventilation has greatly increased, success with this approach is limited [39,40]. Nasal intermittent positive pressure ventilation could potentially improve noninvasive respiratory support [68,69].…”
Section: The Future: Any Leaps In Sight?mentioning
confidence: 99%